Budgetary allocation and quality of secondary education in Oyo State, Nigeria (2019)
This study investigated the impact of budgetary allocation and quality of secondary education in public secondary school in Oyo state. Nigeria. The study employed descriptive survey research design. The population of the study comprised all the public secondary schools principals and teachers in Oyo State and Ministry of Education staffs (TESCOM officers). The study adopted multi-stage sampling procedure. The sample size of the study comprised 30principals. 420 teachers and 50 TESCOM officers which mode up a total of 500 respondents from 8 local governments of the state and 30 secondary schools. Six (6) research questions were raised and answered and Data were analyzed using descriptive statistics. The study findings indicated that quality of secondary education in Oyo State is low. There was fluctuations in budgetary allocations to education; within its components (infrastructural facilities. furniture and flitting’s, staff recruitment. wages and salaries, and teaching-learning materials) and in its totals under the years reviewed (2011-2017). The study finding revealed that budgetary allocation has not promoted that quality of furniture and fittings in Oyo State. Budgetary allocation has not improved the quality of teachers in Oyo State. Budgetary allocation has not improved teaching-learning materials in Oyo State. In light of findings, the study forwarded the following recommendations. Government should make effort to improve secondary education budgetary allocation by adopting a policy of proactive investment in secondary education. Government should have that political will and test 26%funding of education using annual budget of nation's resource for at least five years and assess the impact amongst others